Antibiotic resistance in Zn(II)-deficient environments: Metallo-β-lactamase activation in the periplasm - Meini, María Rocío (2013)
Zn(II) is an essential metal ion in living organisms, playing a wide variety of roles as a structural, regulatory or catalytic cofactor in proteins, that is able to interact with approximately 10% of the entire proteome in humans [1]. As is the case for most transition metal ions, high Zn(II) levels are toxic. Therefore, organisms have developed a series of mechanisms to regulate Zn(II) concentrations and to ensure proper metal uptake by metalloproteins [2]. These mechanisms involve specific metal sensor proteins, import and export machineries that allow subcellular compartmentalization and a pool of small molecules and/or proteins that are able to bind excess Zn(II) [2]. As a result, there is rarely free Zn(II) within cells and biological fluids [3].